2017
DOI: 10.7287/peerj.preprints.3421v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

Short-term gains in histology knowledge: A veterinary gaming application

Abstract: Outcomes research exists incorporating non-digital games in veterinary education; however, little research examines outcomes from digital applications. Bauman's Layered-Learning Model was applied to investigate whether a digital matching game produced short-term knowledge gains in veterinary students. Two groups of students (n1=67; n2=55) practiced the matching game for an hour. A Wilcoxon signed rank test tested for a statistically significant improvement in pretest/post-test scores. All statistical analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Bauman’s layered-learning model was chosen as a theoretical framework for this study This model describes a matrix for scaffolding traditional didactic presentation of course materials with multimedia educational technology [1820]. The model presupposes that traditional didactic learning techniques, such as knowledge transfer through scholarly reading and interaction with faculty and staff, still have relevance in the modern classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Bauman’s layered-learning model was chosen as a theoretical framework for this study This model describes a matrix for scaffolding traditional didactic presentation of course materials with multimedia educational technology [1820]. The model presupposes that traditional didactic learning techniques, such as knowledge transfer through scholarly reading and interaction with faculty and staff, still have relevance in the modern classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Um outro exemplo de jogo digital desenvolvidoé o Histology Card! [Bauman et al 2017], no qual os jogadores recebem uma placa de imagem histológica a qual precisam complementar com imagens apresentadas em cartões histológicos correspondentes.…”
Section: Trabalhos Relacionadosunclassified
“…The VR-SUCI game was designed to give students time to practice and reinforce steps of the sterile urinary catheter insertion skill that nursing students had previously been taught. Bauman’s layered-learning model was used as a framework, which suggests that virtual technology may be most useful when used to reinforce previously learned skills (Bauman et al, 2018: Bauman, 2016; Bauman et al, 2014; Bauman, Gilbert, & Vaughan, 2017), not to initially teach the skill of sterile catheterization. In testing the first version of the game, participants expressed a need for technical support to manage wires and gloves that provided haptic feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Bauman suggested that games are most useful when they are part of a layered-learning approach; in other words, they support various forms of learning and serve as cognitive aids (Bauman et al, 2014). Bauman’s layered-learning model connects theoretical didactic preparation (readings, assignments, lectures), interactive applications via digital games or simulation-based experiences, simulation through manikins or standardized patients, and real-world experiences to create a comprehensive learning approach (Bauman, 2016; Bauman et al, 2014, 2017).…”
Section: Introductionmentioning
confidence: 99%